Molecular dynamics simulation of RNA ribosomal frameshift stimulatory elements - Seah, Yi Ling (2017)
The RNA hairpin-type pseudoknots and stem-loops structures are essential downstream elements for minus-one ribosomal frameshifting. While frameshifting efficiency and mechanical stability of these structures were investigated in vivo and in vitro, in silico studies were limited. Here, steered molecular dynamics simulations were performed to unfold hTR ΔU177 pseudoknot and its mutants. Microscopic molecular structures and the dynamic unfolding process, which are not observed under experimental conditions, were illustrated. Furthermore, less force was required to unfold the native pseudoknot mutants due to the destabilization of base triples. This suggests that pseudoknot stability is strongly dependent on stem-loop interactions. HIV RNA frameshifting stem-loop was also investigated. The presence of an anti-frameshifting ligand, DB213, was found to slightly stabilize the stem-loops, increasing the force required in our pulling simulations. Taken together, the link between mechanical stability, three-dimensional structure and frameshifting efficiency was examined, which may provide a better understanding of minus-one ribosomal frameshifting.